COMPETENCE AND JOB SATISFACTION ON THE PERFORMANCE OF MEDICAL AND HEALTH PERSONNEL OF THE SOUTHEAST SULAWESI REGIONAL POLICE - Machmud, Sri Wulan; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Abstract Human Resources are one of the most valuable assets possessed by an organization, as they are the only resources capable of mobilizing other resources. Therefore, human resources are a key factor that organizations must maintain in line with the demands they constantly face to respond to every challenge. Thus, efforts to retain quality human resources are the primary steps for an organization. This research aims to analyze the influence of competence and job satisfaction on the performance of Medical and Health Personnel in the Southeast Sulawesi Regional Police. The study adopts a quantitative approach with 70 respondents. The analytical technique used is Partial Least Square (PLS). The findings indicate that high competence and job satisfaction positively contribute to personnel performance. The Medical and Health field has the responsibility to provide professional health support based on knowledge and technology, as well as to deliver comprehensive healthcare services to members of the Indonesian National Police in the Southeast Sulawesi Regional Police, to maintain their health and optimize their performance for overall good results. Additionally, the research results have reflected the alignment between the responsibilities and functions of each section by following the main tasks and functions established. In the future, further research can examine additional factors other than the model studied, such as adding leadership and motivation. Kata Kunci: Competence, Job Satisfaction, Personnel Performance